NOVA OPHIUCHI 1958 - ROSA, E DE LA (Observatorio Astrofísico de Tonantzintla, Pue, Pue, Mex, 1956)
The light curve is presented for Nova Ophiuchi 1958 from the Schmidt plates of the Tonantzintla Observatory. Maximum appears at 17-18 November 1957.
BOL OBS TONAN TACUB
Keywords: NOVA, OPHIUCHI, 1958; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS